72.2k views
3 votes
Find the product. (-7p)^3

User Adivasile
by
4.8k points

1 Answer

5 votes

For this case we must resolve the following expression:


(-7p) ^ 3

So:


(-7p) ^ 3 =\\(-7p) (- 7p) (- 7p) =

By law of multiplication of signs we have:


- * - = +\\+ * - = -

Also:


7 * 7 * 7 = 343\\p * p * p = p ^ 3

Finally, we have that the expression is equivalent to:


(-7p) ^ 3 = -343p ^ 3

ANswer:


-343p ^ 3

User Alen Smith
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.